Surface reconstruction of titania with g-C3N4 and Ag for promoting efficient electrons migration and enhanced visible light photocatalysis - Leong, K.H.; Liu, S.L.; Sim, L.C.; Saravanan, P.; Jang, M.; Ibrahim, S. (2015)
The developments of heterogeneous photocatalysts are one among the competent reconstruction approach to enrich the visible light responsiveness of conventional TiO2. In the present work the TiO2 was reconstructed with graphitic carbon nitride (g-C3N4) and silver (Ag) to form a ternary (g-C3N4)-Ag/TiO2. The graphitic carbon nitride an intriguing material was prepared through a facile pyrolysis by using urea as a precursor. The silver (Ag) that plays a role as electron-conduction mobiliser in the ternary was synthesised through solar mediated photodeposition method. The synthesised ternary composite characteristics were thoroughly investigated through various physical and chemical analyses. The presence of g-C3N4 in the ternary photocatalysts promoted the formation of interface between the Ag/TiO2 and g-C3N4 and stimulated the electron transfer between them. These electrons migration acknowledged by the synergic effect prolonged the lifetime of charge carriers. The g-C3N4 also significantly tuned the energy band of conventional TiO2. The prepared ternary exhibited significantly high visible light photocatalytic performance by degrading Amoxicillin (AMX) a poor photosensitising pollutant at highest rate. (C) 2015 Elsevier B.V. All rights reserved.